TINGKAT PENDIDIKAN, UPAH, INFLASI, DAN PERTUMBUHAN EKONOMI TERHADAP PENGANGGURAN DI INDONESIA - Suhendra, Indra Hadi; Wicaksono, Bayu Hadi (Ekonomi-Qu (Jurnal Penelitian Ilmu Ekonomi), 2016)
This study aimstodetermine the effect of the Education level,Wages, Inflation, and Economic Growth Against Unemployment in Indonesia over Period 2010 until 2012. The analytical methodusedis linear regressionanalysis with panel data method by Eviews 8. The Results from this study showed that during 2010 until2012, level Educations (TPS1), wages, inflation and economic growth have a significant effect on the unemployment and the level education of (TPSMA) has notsignificant impact on the unemployment rate. Simultaneously the independent variable has significant effect on the dependent variable. The coefficient of determination (R2) was 0.722353. This shows that amounted to 72.2353% of independent variables isable to explain the dependent variable.